Upaya Meningkatkan Hasil Belajar IPS Ekonomi Menggunakan Model Pembelajaran Kooperatif Tipe Co-Op Co-Op pada Kelas VIII IPS-2 SMP Islam Nurul Ihsan Palangka Raya - Rizki Amalia; Muhamad Ramli (Neraca: Jurnal Pendidikan Ekonomi, 2019)
This study aims to (1) To find out how the learning activities of class VIII IPS-2 students of ISLAMIC NURUL IHSAN SMP Palangka Raya using cooperative learning models Co-op Co-op type. (2) To improve the economics of Class VIII IPS social studies learning outcomes of 2 students in the Islamic Middle School of NURUL IHSAN in Palangka Raya using a cooperative learning Co-op type Co-op model. This type of research is classroom action research (CAR). The students of class VIII IPS-2SMP ISLAMIC NURUL IHSAN Palangka Raya with a total of 30 students. Data collection techniques used are observation and tests. Data analysis used is qualitative analysis and quantitative analysis. (1) The activity of both students during economic social studies learning using a cooperative learning Co-op type Co-op model. The first cycle scores 3 on average with good criteria. In the second cycle, the average score was 3 with good criteria. (2) There are increases in students' economic social studies learning outcomes after using cooperative learning Co-op type Co-op model. The results of this study are as follows: (below the KKM value> 70) with 23% classical completeness with the criteria not reached. Cycle I obtained an average value of 67 with 63% classical completeness with criteria not reached. Cycle II obtained an average value of 87 with 100% classical completeness with the criteria reached.